2017
DOI: 10.1016/j.ejmech.2017.03.078
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethyl arylamides with antileukemia effect and intracellular inhibitory activity over serine/arginine-rich protein kinases (SRPKs)

Abstract: The serine/arginine-rich protein kinases (SRPKs) have frequently been found with altered activity in a number of cancers, suggesting they could serve as potential therapeutic targets in oncology. Here we describe the synthesis of a series of twenty-two trifluoromethyl arylamides based on the known SRPKs inhibitor N-(2-(piperidin-1-yl)-5-(trifluoromethyl)phenyl)isonicotinamide (SRPIN340) and the evaluation of their antileukemia effects. Some derivatives presented superior cytotoxic effects against myeloid and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
1
15
0
6
Order By: Relevance
“…SRPK2 promoted the cell proliferation of leukemia by regulating cyclin A1 (not cyclin A2) expression [11]. Consistent with the present study, SRPIN340, an inhibitor of SRPKs, showed antileukemic effects [32]. In hepatocellular carcinoma, SRPK2 silencing elevated Numb expression, which decreased cell migration and invasion by down-regulating Akt phosphorylation and c-Myc expression [33].…”
Section: Discussionsupporting
confidence: 84%
“…SRPK2 promoted the cell proliferation of leukemia by regulating cyclin A1 (not cyclin A2) expression [11]. Consistent with the present study, SRPIN340, an inhibitor of SRPKs, showed antileukemic effects [32]. In hepatocellular carcinoma, SRPK2 silencing elevated Numb expression, which decreased cell migration and invasion by down-regulating Akt phosphorylation and c-Myc expression [33].…”
Section: Discussionsupporting
confidence: 84%
“…SRPK1 inhibitors are being investigated as new anticancer agents. 26 , 27 Morooka et al 27 screened a large-scale chemical library to identify a new inhibitor of SRPK1, and the screened inhibitor SRPIN340 was found to prevent VEGF production more effectively in a mouse model of age-related macular degeneration, suggesting that silencing of SRPK1 could prevent neovascularization; this indicated that SRPK1 was a potential target for antiangiogenic drug development. The approach of the SRPK1 inhibitor “SPHINX” was also investigated to inhibit angiogenesis for prostate cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, SRPK1 pharmacologic inhibition with SPHINX31 did not impact normal hematopoiesis in the long term [65]. In other studies, SRPK1 downregulation suppressed proliferation and enhanced apoptosis in various leukemia types [66][67][68]. Siqueira et al also noted that the effect on apoptosis took place in a synergistic fashion with chemotherapy [67].…”
Section: Srpk1-mediated Mechanism(s)/ Pathway(s) Involved Referencementioning
confidence: 95%
“…The SRPK1-induced PI3K/AKT pathway interacts with miR-1296 [45] ↑SRPK1 was found in hepatocellular cancer cell lines [46] ↑SRPK1 was found in hepatocellular cancer cell lines and promoted proliferation ↓SRPK1 suppressed proliferation in vitro and growth in vivo and in vitro SRPK1 interacts with the PI3K/AKT pathway [47] Esophagus ↑SRPK1 was found in esophageal cancer cell lines and promoted proliferation ↓SRPK1 suppressed proliferation, migration, and invasion and enhanced apoptosis in vitro also suppressed tumor growth in vivo SRPK1 interacts with the TGF-β pathways [48] Pancreas ↑SRPK1 was found in pancreatic cancer cell lines ↓SRPK1 suppressed proliferation and enhanced apoptosis and sensitivity to chemotherapy in vitro SRPK1 interacts with SR proteins and regulates apoptosis [22] SRPK1 interacts with the AKT and MAPK pathways [36] Blood (Leukemia) ↓SRPK1 suppressed proliferation in vitro and tumor growth in vivo, while it enhanced cell cycle arrest, apoptosis and prolonged the survival of animal models in MLL-rearranged AML; ↓SRPK1 switched BRD4 splicing, favoring the production of its long isoform SRPK1 modulates the alternative splicing of BRD4, MYB, and MED24 [65] ↑SRPK1 was found in various myeloid and lymphoid leukemia cell lines ↓SRPK1 was cytotoxic and enhanced apoptosis in vitro SRPK1 interacts with the SR proteins and modulates the expression and splicing of MAP2Ks, VEGF, and FAS [66] ↓SRPK1 suppressed proliferation while it enhanced autophagy and apoptosis in a synergistic fashion with chemotherapy in vitro SRPK1 interacts with SR proteins and modulates the expression of MAP2Ks and VEGF and the splicing of RON [67] ↓SRPK1 suppressed proliferation and enhanced apoptosis in vitro in CML SRPK1 interacts with the PARP-caspase-3 pathway [68] Kidney ↑SRPK1 was found in renal cancer cell lines ↓SRPK1 suppressed proliferation, migration, and invasion in vitro, also tumor growth in vivo SRPK1 interacts with PI3K/AKT pathway [50] Brain (Glioma) ↑SRPK1 was found in glioma cell lines ↓SRPK1 suppressed proliferation, migration, and invasion of glioma cells in vitro while it induced resistance to chemotherapy [51] ↓SRPK1 suppressed tumor growth and apoptosis in vivo, also angiogenesis in vitro and in vivo…”
Section: ↓Srpk1 Suppressed Migration and Invasion In Vitromentioning
confidence: 99%